Device Performance of Emerging Photovoltaic Materials (Version 2). Issue 48 (11th November 2021) - Almora, Osbel; Baran, Derya; Bazan, Guillermo C.; Berger, Christian; Cabrera, Carlos I.; Catchpole, Kylie R.; Erten‐Ela, Sule; Guo, Fei; Hauch, Jens; Ho‐Baillie, Anita W. Y.; Jacobsson, T. Jesper; Janssen, Rene A. J.; et al.
Abstract: Following the 1st release of the "Emerging photovoltaic (PV) reports", the best achievements in the performance of emerging photovoltaic devices in diverse emerging photovoltaic research subjects are summarized, as reported in peer‐reviewed articles in academic journals since August 2020. Updated graphs, tables, and analyses are provided with several performance parameters, e.g., power conversion efficiency, open‐circuit voltage, short‐circuit current density, fill factor, light utilization efficiency, and stability test energy yield. These parameters are presented as a function of the photovoltaic bandgap energy and the average visible transmittance for each technology and application and are put into perspective using, e.g., the detailed balance efficiency limit. The 2nd instalment of the "Emerging PV reports" extends the scope toward tandem solar cells and presents the current state‐of‐the‐art in tandem solar cell performance for various material combinations. Abstract : The 2nd instalment of the "Emerging PV reports" continues presenting and analyzing the best research achievements in the performance of emerging single‐junction and monolithic tandem solar cells, as reported in peer‐reviewed articles in academic journals since August 2020.